Phenomenon of Women-Leaders in Romania and Russia: Equal Gender Opportunities in Emerging Markets - Irina BUDRINA (Revista de Management Comparat International)
With women now accounting for nearly half of the paid labor force in developed countries and 40% or more of managerial positions (though far fewer in top management) it is becoming more and more important to take into consideration the phenomenon of Women Leadership. The West Europe has been under examination and analysis for quite some time due to the EU policy of equal gender rights and the institutional and economic development of this part of Europe. The uniqueness and difference of the political, economic and social changes in Eastern Europe provides an attractive and different field for research. Romania and Russia are the countries in transition from one economy (post socialism or postcommunism) to the emerging markets or so called developing countries. What are the leadership qualities that are welcomed by the private and public sectors there? What is the profile of women-leaders in these countries, women who had to quit their state jobs and start their own business as a survival urge? What is the influence of women-leaders-entrepreneurs on their own companies’ financial results in the emerging markets?